2003
DOI: 10.1259/dmfr/24534480
|View full text |Cite
|
Sign up to set email alerts
|

Temporomandibular internal derangement: correlation of MRI findings with clinical symptoms of pain and joint sounds in patients with bruxing behaviour

Abstract: It was demonstrated that a higher prevalence of condylar bony changes occurred in reducing joints in patients with bruxing behaviour.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
43
2
6

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(61 citation statements)
references
References 31 publications
7
43
2
6
Order By: Relevance
“…• Occlusal discrepancies [1,6,8,27,29] • Mouth breathing and therefore a higher likelihood of dry mouth [8] • Temporomandibular disorders [30,31] Psychological factors:…”
Section: Local Factorsmentioning
confidence: 99%
“…• Occlusal discrepancies [1,6,8,27,29] • Mouth breathing and therefore a higher likelihood of dry mouth [8] • Temporomandibular disorders [30,31] Psychological factors:…”
Section: Local Factorsmentioning
confidence: 99%
“…In a single work in literature that was done to correlate magnetic resonance imaging (MRI) findings of effusion, disc displacement, condylar bony changes and disc form with clinical findings of pain and sounds in patients with bruxing and non-bruxing behavior, the authors found that a higher prevalence of condylar bony changes occurred in reducing joints in patients with bruxing behavior and also they highlighted the importance of phonoarthrography in diagnosing unilaterally affected joints. In non-reducing joints, 30% of painful joints in the patient group and 59% of controls showed a strong signal in the joint space on T 2 weighted imaging (Guler et al, 2003).…”
Section: Phonoarthrography Versus Musculoskeletal Ultrasonography Andmentioning
confidence: 87%
“…Later, microphones have been used to reduce subjectivity; that step was taken by Erb (1933), when he used a contact microphone obtaining the clearest sound, with the exception of cases of meniscal tears, when he placed the sensor over the patella. Most of the joints recorded were the knees (M H Bassiouni & El-Feki, 1986;M H Bassiouni et al, 1995;Krishnan et al, 2000;Nagata, 1988) and temporomandibular joints (Ciancaglini et al, 1987;Guler et al, 2003). The first reason, they are superficial thus perfect for auscultation and recording and the second reason is that they produce sounds when diseased.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5][6][7][8] Whereas some other studies reported that there was not any correlation between bruxism and TMD symptoms and signs, 2,9) and another reported unclear results as for unequivocal support/rejection of the correlation between bruxism and TMD. 2,10,11) One of the reasons of uncertainty of correlation between bruxism and TMD is lack of definitively reliable methods for assessing bruxism.…”
Section: Introductionmentioning
confidence: 99%